Compromised Astrocyte Swelling/Volume Regulation in the Hippocampus of the Triple Transgenic Mouse Model of Alzheimer’s Disease - Tureckova, Jana; Kamenicka, Monika; Kolenicova, Denisa; Filipi, Tereza; Hermanova, Zuzana; Kriska, Jan; Meszarosova, Lenka; Pukajova, Barbora; Valihrach, Lukas; Androvic, Peter; Zucha, Daniel; Chmelova, Martina; et al. (Frontiers in Aging Neuroscience, 2022)
In this study, we aimed to disclose the impact of amyloid-β toxicity and tau pathology on astrocyte swelling, their volume recovery and extracellular space (ECS) diffusion parameters, namely volume fraction (α) and tortuosity (λ), in a triple transgenic mouse model of Alzheimer’s disease (3xTg-AD). Astrocyte volume changes, which reflect astrocyte ability to take up ions/neurotransmitters, were quantified during and after exposure to hypoosmotic stress, or hyperkalemia in acute hippocampal slices, and were correlated with alterations in ECS diffusion parameters. Astrocyte volume and ECS diffusion parameters were monitored during physiological aging (controls) and during AD progression in 3-, 9-, 12- and 18-month-old mice. In the hippocampus of controls α gradually declined with age, while it remained unaffected in 3xTg-AD mice during the entire time course. Moreover, age-related increases in λ occurred much earlier in 3xTg-AD animals than in controls. In 3xTg-AD mice changes in α induced by hypoosmotic stress or hyperkalemia were comparable to those observed in controls, however, AD progression affected α recovery following exposure to both. Compared to controls a smaller astrocyte swelling was detected in 3xTg-AD mice only during hyperkalemia. Since we observed a large variance in astrocyte swelling/volume regulation, we divided them into high- (HRA) and low-responding astrocytes (LRA). In response to hyperkalemia, the incidence of LRA was higher in 3xTg-AD mice than in controls, which may also reflect compromised K+ and neurotransmitter uptake. Furthermore, we performed single-cell RT-qPCR to identify possible age-related alterations in astrocytic gene expression profiles. Already in 3-month-old 3xTg-AD mice, we detected a downregulation of genes affecting the ion/neurotransmitter uptake and cell volume regulation, namely genes of glutamate transporters, α2β2 subunit of Na+/K+-ATPase, connexin 30 or Kir4.1 channel. In conclusion, the aged hippocampus of 3xTg-AD mice displays an enlarged ECS volume fraction and an increased number of obstacles, which emerge earlier than in physiological aging. Both these changes may strongly affect intercellular communication and influence astrocyte ionic/neurotransmitter uptake, which becomes impaired during aging and this phenomenon is manifested earlier in 3xTg-AD mice. The increased incidence of astrocytes with limited ability to take up ions/neurotransmitters may further add to a cytotoxic environment.